2011
DOI: 10.1074/jbc.m110.210518
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Suppresses Activation of Nuclear Factor of Activated T Cells 1 (NFAT1) in Human CD4+ T Cells

Abstract: Minocycline is a tetracycline family antibiotic that has antiinflammatory and immunomodulatory properties. These properties have shown promise in the treatment of conditions such as rheumatoid arthritis, Huntington disease, and multiple sclerosis. As lymphocyte activation is involved in the pathogenesis of many of these diseases, T cells are postulated to be a primary target in minocycline therapy. Previous studies have demonstrated attenuation of CD4 ؉ T cell activation by minocycline, but a specific mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 60 publications
4
25
0
1
Order By: Relevance
“…Our work sets the stage for identifying the putative agent(s) underlying the process. Doxycycline and/or other tetracyclines also act by arresting T cell proliferation in AAA lesions by inhibiting mitochondrial protein synthesis (8,9) or suppressing NF of activated T cells in human CD41 T cells (10), doxycycline inhibits also monocytes and granulocytes (5,8,9) We agree with Drs. Koon and Taanman that doxycycline may be effective in inhibiting T cells in AAA as well as other autoimmune diseases where clonal expansions of T cells have been demonstrated and should be evaluated further for this purpose.…”
supporting
confidence: 63%
“…Our work sets the stage for identifying the putative agent(s) underlying the process. Doxycycline and/or other tetracyclines also act by arresting T cell proliferation in AAA lesions by inhibiting mitochondrial protein synthesis (8,9) or suppressing NF of activated T cells in human CD41 T cells (10), doxycycline inhibits also monocytes and granulocytes (5,8,9) We agree with Drs. Koon and Taanman that doxycycline may be effective in inhibiting T cells in AAA as well as other autoimmune diseases where clonal expansions of T cells have been demonstrated and should be evaluated further for this purpose.…”
supporting
confidence: 63%
“…However, the susceptibility of protozoa species which lack mitochondria (e.g., Trichomonas vaginalis, Giardia lamblia, Entamoeba histolytica) (7,66), as well as viral pathogens (Table 1), raises further questions about the exact molecular mechanism(s) of action of the tetracy-clines. In contrast to the proffered antiprotozoal activity via mitochondrial and endosymbiont rRNA binding, the antiviral activities of the tetracyclines have not been associated with rRNA binding (2,13,14,(68)(69)(70). Rather, the antiviral activity has been attributed in part to anti-inflammatory (4, 15), antiapoptotic (2), and neuroprotective (1) properties.…”
Section: Mechanism(s) Of Action Of the Tetracyclines: The Journey So Farmentioning
confidence: 96%
“…It is possible that minocycline suppresses both viral replication and activation of the inflammatory and cellular responses to these viral infections via an effect on dsRNAs (14). Hence, the antiapoptotic, anti-inflammatory, and antiviral activities of minocycline that have been observed in viral infections (2,13,14,(68)(69)(70) may also be mediated via interactions with dsRNAs. Further investigations in line with the dsRNA binding perspectives are, therefore, quite imperative.…”
Section: Mechanism(s) Of Action Of the Tetracyclines: The Journey So Farmentioning
confidence: 99%
“…Minocycline and doxycycline reduce NF-κB activity in THP-1 cells stimulated with sonicated Borrelia burgdorferi (Bernardino et al 2009). Moreover, minocycline also inhibits NF-κB activation in microglial cells (Si et al 2004;Nikodemova et al 2006), though this effect has not been observed in human CD4+ T cells (Szeto et al 2011).…”
Section: Intracellular Signalling Pathways Affected By Tetracyclinesmentioning
confidence: 96%
“…In fact, some molecular targets have been suggested. Recently, Szeto et al (2011) have shown that in human CD4+ T cells, minocycline reduces nuclear factor of activated T-cells 1 (NFAT1) activation, which is a key regulatory factor in T cell activation. This reduction in NFAT1 activation might be due to the increased glycogen synthase kinase-3 activity and attenuation of intracellular Ca 2+ influx induced by minocycline.…”
Section: Intracellular Signalling Pathways Affected By Tetracyclinesmentioning
confidence: 99%